Case and agreement from fringe to core : a minimalist approach - Keine, Stefan (Linguistische Arbeiten (Max Niemeyer Verlag), 2010)
This book develops a unified theory of non-canonical case and agreement patterns that have remained elusive so far. Drawing from a wide range of typologically non-related languages, it sets forth the claim that the phenomenaunder discussion involve abstract deletion operations which interact with othergrammatical operations in intricate but highly systematic ways. This interplay isshown to give rise to seemingly non-related surface phenomena, thus integratingthese phenomena within a more general framework of argument encoding.